(untitled) (Conference on English Language Teaching, 2023)
Over the past two decades, a great number of researchers had conducted studies on multilingualism. Nevertheless, research on multilingualism in EFL learners appeared to be scant. This study focused on investigating what was multilingualism found in the EFL learners in Pesantren and how did the post-humanism perspective give a solution to multilingualism in EFL learners. The method used in this study was descriptive qualitative. This study included second-semester university students living in Pesantren (an Indonesian Islamic boarding school). The study showed that, in the context of Pesantren, where the first language, Arabic, English, and Indonesian are typically the primary languages of instruction for communication. A post-humanism perspective as the solution to multilingualism might involve giving learners authentic and meaningful opportunities to use and develop their language skills, such as by participating in multilingual and multicultural communities or using digital technology and social media platforms that support multilingual expression and communication.